Postoperative Pain Survival and Correlating Factors in Endometriosis Patients: Kesintasan Keluhan Nyeri Pasca Pembedahan pada Pasien Endometriosis serta Faktor-Faktor yang Mempengaruhi - Kanadi Sumapradja; Fitriana M. Nuryadi (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: To determine the survival of pain complaints at 3, 6, 9 and 12 months and the correlation between age at diagnosis, age of menarche, parity, stage of disease and post-operative medication in endometriosis patient at RSUPN Dr. Cipto Mangunkusumo. Methods: This was a prospective cohort study with survival analysis method of 139 women of productive age with endometriosis who came to Gynecology Outpatient Clinic in Dr. Cipto Mangunkusumo Hospital from January 2015 to January 2017. The patients were observed at 3 months, 6 months, 9 months and 12 months after the surgery. Results: Survival of pain complaints at 3, 6, 9 and 12 months after endometriosis operation was 99.2%, 96.6%, 93% and 88.4% respectively. There was no significant correlation between post-operative pain survival and age of diagnosis (p=0.138), age of menarche (p=0.492), parity (p=0.110) and stage of disease (p=0.908). There was a significant correlation between post-operative medical therapy and pain complaints survival. Subjects who were given medication had a risk of 0.26 times (CI 95% 0.081-0.857) pain recurrence compared to those who were not. Conclusion: Pain complaints survival were significantly associated with post-operative medical therapy, but not associated with age, age of menarche, parity and stage of disease. Keywords: endometriosis, postoperative medical therapy, postoperative pain, survival Abstrak Tujuan: Mengetahui kesintasan keluhan nyeri pada 3, 6, 9 dan 12 bulan dan hubungan antara usia saat diagnosis, usia menarke, paritas, stadium penyakit dan terapi medisinalis pasca pembedahan pada pasien endometriosis di RSUPN Dr. Cipto Mangunkusumo. Metode: Penelitian kohort prospektif pada 139 wanita usia produktif dengan metode analisis kesintasan pada pasien endometriosis yang datang ke Poliklinik Ginekologi RSUPN Cipto Mangunkusumo pada bulan Januari 2015 hingga Januari 2017. Pasien kemudian diobservasi pada bulan ke 3, 6, 9 dan 12 setelah operasi. Hasil : Kesintasan keluhan nyeri pada bulan ke 3, 6, 9 dan 12 berturut-turut adalah 99,2%, 96,6%, 93% dan 88,4%. Tidak ada hubungan yang bermakna antara kesintasan nyeri pasca pembedahan dengan usia saat diagnosis (p=0,138), usia saat menarke (p=0,492), paritas (p=0,110) dan stadium penyakit (p=0,908). Terdapat hubungan yang bermakna antara terapi medisinalis pasca pembedahan dan kesintasan keluhan nyeri. Subyek yang mendapatkan terapi medisinalis pasca pembedahan memiliki risiko 0,26 kali mengalami kekambuhan nyeri dibandingkan dengan yang tidak. Kesimpulan : Kesintasan keluhan nyeri memilki hubungan yang bermakna dengan terapi medisinalis pasca pembedahan namun tidak memiliki hubungan dengan usia saat diagnosis, usia menarke, paritas dan stadium penyakit. Kata kunci: endometriosis, kesintasan, nyeri pasca pembedahan, terapi medisinalis pasca pembedahan